Elephantine revisited new insights into the Judean community and its neighbors - Folmer, Margaretha (Eisenbrauns, 2022)
"A collection of essays examining the fifth-century BCE Judean community in Elephantine in southern Egypt. Provides new insights into the origin and identity of the community as well as archaeology, criminal and family law, religious life, the Bible, and the Aramaic language"--
Keywords: Geschichte 500 v. Chr.-400 v. Chr.; Juden; Elephantine; Jews / Egypt / Elephantine / History / To 1500; Aramaic language / Egypt / Elephantine; Elephantine (Egypt) / Antiquities; Elephantine (Egypt) / Social life and customs; Éléphantine (Égypte) / Murs et coutumes; Konferenzschrift -- 07.07.2013-10.07.2021 -- St. Andrews; Aufsatzsammlung